Vascular Access Site Injury After Transfemoral Transcatheter Aortic Valve Insertion. Issue 4 (10th June 2013) - Greason, Kevin L.; Suri, Rakesh M.; Huebner, Marianne; Reeder, Guy S.; Williamson, Eric E.; Nkomo, Vuyisile T.; Rihal, Charanjit S.; Mathew, Verghese
Abstract Background Vascular complications associated with transfemoral transcatheter aortic valve insertion (TAVI) are a frequent untoward consequence of arterial sheath insertion. We report the prevalence of anatomic arterial injury with open artery access TAVI. Methods This review consisted of 53 consecutive patients who received transfemoral Sapien 23 or 26 mm TAVI via the 22‐ or 24‐French sheath through open artery access from November 2008. The median age of the patients was 83 years (range, 59 to 94), and there were 31 males (58%). All arteries were examined to determine the optimal point of access and then explored after removal of the sheath to document injury. Results The accessed artery had a minimal lumen diameter of 8.9 mm (7.2 to 14.7) and a sheath‐to‐artery ratio of 1.0 (0.6 to 1.2). The point of access was the common femoral artery in 33 patients (62%) and the external iliac artery in 20 (38%). Exploration of the artery demonstrated localized arterial injury in 22 patients (42%). Female gender was predictive of injury (p = 0.03), but arterial access site location, presence of arterial access calcification, sheath‐to‐artery ratio, and sheath size were not. Techniques of artery repair included primary closure in 34 patients (64%), pericardial patch angioplasty in 15 (28%), and graft interposition in 4 (8%). There was one minor groin wound complication. Conclusions Open artery access allows for direct examination and optimal access site choice of the vessel during transfemoral TAVI. Localized arterial injury was commonly encountered after 22‐ and 24‐French sheath insertion, but the associated artery repair complication rate was low. doi: 10.1111/jocs.12140 (J Card Surg 2013;28:348–352)